Maternal uterine artery Doppler in the first and second trimesters as screening method for hypertensive disorders and adverse perinatal outcomes in low-risk pregnancies - Scandiuzzi, Rosiane Maciel (Obstet Gynecol Sci, 2016)
OBJECTIVE: To assess the maternal demographic characteristics and uterine artery (UA) Doppler parameters at first and second trimesters of pregnancy as predictors for hypertensive disorders (HDs) and adverse perinatal outcomes. METHODS: This prospective cohort study comprised 162 singleton low-risk women undergoing routine antenatal care. The left and right UA were assessed by color and pulsed Doppler and the mean pulsatility and resistance indices as well as the presence of a bilateral protodiastolic notch were recorded at 11 to 14 and 20 to 24 weeks' gestation. Multilevel regression analysis was used to determine the effects of maternal characteristics and abnormal UA Doppler parameters on the incidence of HD, small for gestational age newborn, cesarean section rate, Apgar score <7 at 1st and 5th minute, and admission to the neonatal intensive care unit. RESULTS: Fifteen women (9.2%) developed HD. UA mean resistance index (RI), UA mean pulsatility index, and parity were independent predictors of HD. Compared to the pregnancies with a normal UA mean RI at the first and second trimesters, pregnancies with UA mean RI >95th percentile only at the first trimester showed an increased risk for HD (odds ratio, 23.25; 95% confidence interval, 3.47 to 155.73; P<0.01). Similar result was found for UA mean pulsatility index >95th percentile (odds ratio, 9.84; 95% confidence interval, 1.05 to 92.10; P=0.05). The model including maternal age, maternal and paternal ethnicity, occupation, parity and UA mean RI increased the relative risk for HD (area under receiver operating characteristics, 0.81). CONCLUSION: A first-trimester screening combining maternal characteristics and UA Doppler parameters is useful to predict HD in a low-risk population.